SIPONO APPLICATION AS AN INNOVATION IN LEARNING MEDIA OF JAVANESE VOCABULARY PRONUNCIATION (Proceedings of the International Conference on Education, 2023)
Phonological errors in both writing and pronouncing Javanese vocabulary are errors that often occur in various circles of society, especially among students. Errors generally occur in typical Javanese phonemes, namely /a/, /ɔ/, /d/, /D/, /t/, /T/, /e/, /Ə/, and /Ɛ/. This phenomenon can certainly hinder students from achieving Javanese language learning competencies. If this phenomenon is allowed to continue, it can also threaten the existence of good and correct use of the Javanese language in everyday life. One of the contributing factors is the limited availability of learning media. Therefore, there is a need for innovation in the development of technology-based media that can support Javanese language learning. This research aims to describe the development and implication of using the SIPONO application in Javanese language learning at schools, making it a technology-based medium that supports competency achievement. This research uses mixed methods. A qualitative approach is used to obtain problem data and analyze the needs of learning media and a quantitative approach is used to obtain trial data on the use of the application. Data collection techniques included questionnaires and interviews. The informants in this study were linguists, Javanese language teachers, and students. The validity of the data was tested by triangulating the sources. The data analysis technique was carried out with a flow analysis model. The results of the study describe: (1) the development of the Android-based SIPONO application is carried out through the design, design, production, and trial stages; and (2) the SIPONO application has positive implications and can support Javanese language learning as a medium for pronouncing Javanese vocabulary for students. Thus, the SIPONO application is a flexible, android-based media innovation for learning the pronunciation of Javanese vocabulary as well as an effort to preserve the Javanese language through education.
Keywords: android application; Javanese vocabulary; learning media; phonemes; pronunciation